2015
DOI: 10.1513/annalsats.201507-429oc
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Reinfection as an Etiology of Late Recurrent Tuberculosis in the United States

Abstract: Rationale: The etiology of recurrent tuberculosis is typically presumed to be reactivation of residual Mycobacterium tuberculosis infection, but reinfection may account for a greater proportion of recurrent tuberculosis than previously recognized.Objective: To use M. tuberculosis genotyping to characterize the etiology of recurrent tuberculosis occurring 12 months or more after treatment completion. Methods:The study population for this national population-based cohort was drawn from the estimated 3,039 person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
1
17
1
3
Order By: Relevance
“…The dynamic distributions of occurrence time of these two mechanisms have important implications for post-treatment control strategies and clinical trials study design [5]. Similar findings were also reported in previous studies from South Africa and the United States [5, 9, 29]. The findings from settings of both high and low prevalence of HIV infection indicate that exogenous reinfection caused late recurrence, regardless of the prevalence of HIV infection in the setting.…”
Section: Discussionsupporting
confidence: 75%
“…The dynamic distributions of occurrence time of these two mechanisms have important implications for post-treatment control strategies and clinical trials study design [5]. Similar findings were also reported in previous studies from South Africa and the United States [5, 9, 29]. The findings from settings of both high and low prevalence of HIV infection indicate that exogenous reinfection caused late recurrence, regardless of the prevalence of HIV infection in the setting.…”
Section: Discussionsupporting
confidence: 75%
“…In line with these results, a study conducted in California found that US-born patients had a higher recurrence risk than those born outside the US [42]. In contrast, other studies reported an association between foreign-born patients or immigrants and TB recurrences [21,47,50]. It has been reported that immigrants usually have a higher association with TB recurrence caused by reinfection [25,43].…”
Section: Discussionmentioning
confidence: 79%
“…While the possibility of re-infection ( e.g. through travel to high-incidence countries [ 25 ]) cannot be dismissed, both data and local knowledge appears to point to a relatively stable population and therefore potentially genuine observation of late reactivations. While acknowledging the limitations of TST ( e.g.…”
Section: Discussionmentioning
confidence: 99%